3. Conditioned pain modulation paradigm in normal subjects. Issue 12 (December 2016) - Devigili, G.; Rinaldo, S.; Lettieri, C.; Dalla Torre, C.; Eleopra, R.
Abstract : Conditioned pain modulation (CPM) is an experimental paradigm used to assess the endogenous pain inhibition mechanisms. In CPM paradigm a painful conditioning stimulus (CS) may inhibit the perceived pain of a second painful stimulus (test stimulus). In recent years, CPM has been used to improve pain assessment of quantitative sensory testing for making better diagnosis and clinical decision. The aim of study is to provide a reliable CPM paradigm using thermal stimuli and to collect normative data from healthy subjects. Thirty-one healthy subjects are included. Each subject performed a baseline cold and warm thermal thresholds determination. The Medoc webinar CPM system has been used for the CPM session. The CS was a tonic heat pain (NRS > 5). Two thermodes, one used as painful stimulus, the other as CS, were applied in the same limb (forearm and leg) and in contralateral limbs. The test was repeated within 15 days. We found significant heat pain thresholds increase in all subjects (ipsilateral forearm: 8.4%, leg 6.6%; contralateral forearm 5.2%, leg 5.5%). No significant differences have been observed between the test and retest (p > 0.6), with good reliability (ICC 0.72). This CPM paradigm may be applied as a reliable test for diagnostic purpose.